Режимы пуска и тяги двигателя постоянного тока с учетом трехфазного мостового выпрямительно-инверторного преобразователя тяговой подстанции - Кохреидзе, Гиви Климентьевич; Лаошвили, Деми Павлович; Курашвили, Изольда Акакиевна; Пхакадзе, Ш. А. (НТУ "ХПИ", 2010)
In the work there is developed a uniform reversible conversion system of the traction substation according to three-phase bridge circuit, charged at direct-current railway motor of electric locomotive with time proportional control.There are obtained results of electromagnetic and electromechanical processes at starting and traction of the electric motive power taking into account generalized non-commutation and commutation intervals of work.
Starting and traction modes of the direct current motor taking into account the three-phase bridge reversible converter of the traction substation
Keywords: управление широтно-импульсное; состав электроподвижный; ключ транзисторный